Transaksi E-Commerce: Studi Keabsahan Kontrak Elektronik Dalam UU ITE Ditinjau Dari Uncitral Model Law On Electronic Commerce Dan KUH-Perdata - Nasaruddin Nasaruddin (Universitas Muhammadiyah Mataram, 2025)
This study aims to see whether an electronic contract can be said to be valid, especially in Indonesia. Electronic contracts are contracts that arise due to technological and information developments, where buying and selling transactions begin to be carried out through electronic or online media. Since its creation is not like conventional agreements, it is necessary to have clear arrangements regarding the legal terms and legal force of electronic contracts. The research method used is a normative research method and the data in this study was obtained from literature research. Based on the results of the research conducted, it can be concluded that the validity of electronic contracts in e-commerce transactions in Indonesia still faces various challenges of uncertainty regarding the validity and strength of contracts carried out electronically as evidence even though Indonesia already has a clear legal basis, but the ITE Law still holds the problem that from the perspective of the Civil Code and UNCITRAL, the ITE Law does not guarantee legal certainty and firmness regarding the validity of electronic contracts.